2003
DOI: 10.1046/j.1365-2796.2003.01260.x
|View full text |Cite
|
Sign up to set email alerts
|

Coffee and incidence of diabetes in Swedish women: a prospective 18‐year follow‐up study

Abstract: Abstract. Rosengren A, Dotevall A, Wilhelmsen L, Thelle D, Johansson S (Sahlgrenska University Hospital/Ö stra, Göteborg; Göteborg University, Göteborg; AstraZeneca Research and Development, Mölndal; Sweden). Coffee and incidence of diabetes in Swedish women: a prospective 18-year follow-up study. J Intern Med 2004; 255: 89-95.Objectives. To examine the long-term incidence of diabetes in relation to coffee consumption in Swedish women. Design. Prospective longitudinal cohort study. Setting. City of Göteborg, S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
64
2
3

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(80 citation statements)
references
References 46 publications
(47 reference statements)
11
64
2
3
Order By: Relevance
“…This is a new and potentially important addition to the already published finding that coffee consumption is negatively associated with diabetes risk. [4][5][6][7][8] It is based on the following evidence: first, there was a significant statistical interaction between age and beverage consumption; and only subjects r60 y of age exhibited a significant negative relationship between beverage consumption and diabetes risk. The negative relationship was found for ground-caffeinated coffee, ground-decaffeinated coffee, regular tea and caffeine itself.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is a new and potentially important addition to the already published finding that coffee consumption is negatively associated with diabetes risk. [4][5][6][7][8] It is based on the following evidence: first, there was a significant statistical interaction between age and beverage consumption; and only subjects r60 y of age exhibited a significant negative relationship between beverage consumption and diabetes risk. The negative relationship was found for ground-caffeinated coffee, ground-decaffeinated coffee, regular tea and caffeine itself.…”
Section: Discussionmentioning
confidence: 99%
“…Some, [4][5][6][7][8] but not all 9,10 previous studies have found a protective effect from coffee or tea. However, the causal mechanism has not been identified.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…A prospective study performed in the Netherlands reported that coffee drinking was associated with a decreased risk of type 2 diabetes [6]. This finding has since been replicated in several follow-up and cross-sectional studies [7,8,9,10,11]. However, a health examination survey of the Finnish population [12] and a population-based study of Pima Indians [13] failed to observe a protective effect of coffee.…”
Section: Introductionmentioning
confidence: 94%
“…Several recent cohort studies (Van Dam and Feskens, 2002;Carlsson et al, 2004;Rosengren et al, 2004;Salazar-Martinez et al, 2004;Tuomilehto et al, 2004;Hu et al, 2006) and systematic reviews (van Dam and Hu, 2005;Greenberg et al, 2006) have been shown that long-term consumption of coffee may lower the risk of type II diabetes. The mechanism of the association has not been clarified yet, but several plausible mechanisms have been suggested .…”
Section: Introductionmentioning
confidence: 99%